Factors Affecting Reading Interests of Distance Learners: Naseem Akhtar, Muhammad Ather Khan, Fazal-ur-Rahman (PJDOL, 2023)
Reading is not only limited to students in boundary wall institutions, where all individuals cannot access easily. People belongs to poor family backgrounds cannot reach to these institutions for learning and reading while reading is for all, for the better understanding of life. Reading has its value being a source of knowledge and every individual has a right to get knowledge. Book reading does not mean to read only course related books which students are bound to attend classes in boundary wall institutions forpassing exams.